2013
DOI: 10.1080/09712119.2013.822803
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pre-lay diet

Abstract: A biological study was carried out to review the Bureau of Indian Standards (BIS) recommendations for layer pullet feed. Commercial layer chicks were fed till 14 weeks of age as per BIS. At 15 weeks, pullets were randomly assigned to each of the five pre-lay feeding strategies, namely T1 (BIS control), T2 (16/2700), T3 (18/2700) (%CP/ kcal ME/kg), T4 (same as T2 'lysine and methionine by 10% higher than BIS) and T5 (same as T4 with 2% oil). At 5% egg production, all groups were fed as per BIS. Pullets fed on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
5
11
0
Order By: Relevance
“…These findings are in line with those found in the literature, where dietary protein levels prior to sexual maturity did not influence egg production ( Hussein et al, 1996 ; Keshavarz, 1998 ). However, a previous study has shown a positive effect of prelay diet on production performance ( Sujatha et al, 2014 ). They reported that an increase in energy and protein levels in a prelay diet improves production performance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings are in line with those found in the literature, where dietary protein levels prior to sexual maturity did not influence egg production ( Hussein et al, 1996 ; Keshavarz, 1998 ). However, a previous study has shown a positive effect of prelay diet on production performance ( Sujatha et al, 2014 ). They reported that an increase in energy and protein levels in a prelay diet improves production performance.…”
Section: Discussionmentioning
confidence: 96%
“…Dietary manipulation during the prelay period can be an effective way of maintaining flock uniformity and enhancing production performance in the laying flock. The development of secondary reproductive organs and growth of ovarian follicles is thought to be between 4 and 6 wk before the first egg (16–18 wk of age) ( Cave, 1984 ), and rapid physiological changes occur during the prelay phase ( Sujatha et al, 2014 ). The diet’s energy and protein content must be adjusted to ensure that hens consume enough nutrients needed to cope with growth and onset of egg production ( Bain et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual maturity and the beginning of the laying period are critical for laying hens, and may negatively impact hens’ performance [ 1 ]. The pre-peak period is a physically challenging period for young chickens as nutrient deficiencies can affect liver and bone metabolism [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two to three weeks before laying the first egg, there is a significant increase in the weight gain of the egg-laying hens that seek to accumulate body reserves to support the production and size of the eggs during the egg-laying cycle (Summers, 1993). Besides, towards the end of the growth period, there is a rapid development of the ovary and the oviduct and an increase in the size of the liver (Sujatha et al, 2014). From the nutritional point of view, adequate contribution of energy and protein in the diet should be considered at this stage, as this will allow the correct accumulation of body reserves (Cankaya et al, 2008) and appetite stimulation in the animal, to increase its feed intake capacity (Leeson & Summers, 2000;Lazaro & Mateos, 2008).…”
Section: Introductionmentioning
confidence: 99%